Pemanfaatan Pekarangan untuk Budidaya Tanaman Olerikultura sebagai Pendukung Ketahanan Pangan Pada Era Pandemi Covid-19 di Desa Petudua - Juniaty Arruan Bulawan; Hasbiadi Hasbiadi; La Mpia; Fitrianti Handayani (LPPM Universitas Flores, 2022)
The people of Petudua Village on average have a large yard of land, but it has not been used properly. Therefore, the village government facilitates the community by providing various types of olericultural plant seeds or vegetables, to help meet daily nutritional needs, especially during the Covid-19 pandemic. However, the community does not yet know how to cultivate plants properly, so it is necessary to provide assistance in the use of the yard. This service activity aims to assist the Petudua village community to increase knowledge about good plant cultivation, and provide motivation to the community to be able to use their yards to support the availability of family food. The stages of the activities carried out included counseling on the benefits of plant cultivation in the yard, training on how to sow seeds, and training in making organic fertilizers and pesticides from onion skins. The result of this activity is an increase in public knowledge about how to cultivate plants, good nurseries, and how to make organic fertilizers and pesticides from onion skins and can be applied to their respective yards. It is hoped that the Petudua Village government will continue this program, to support food security and improve community welfare.